2-DEOXYGLUCOSE-INDUCED FOOD-INTAKE BY NILE TILAPIA, OREOCHROMIS-NILOTICUS (L) - Delicio, H. C.; Vicentinipaulino, MLM (Associação Brasileira de Divulgação Científica (ABRADIC), 1993)
The alimentary and glycemic responses to cytoglycopenia were studied in thirty-one Nile tilapia alevins of indeterminate sex and age, measuring on average 10.67 +/- 0.82 cm. The cytoglycopenia was provoked by ip injection of 60 mg/kg 2-deoxy-D-glucose (2-DG, N = 16). The control group (N = 15) was submitted to ip injection of 0.2 ml saline. Blood samples for glucose determination were obtained before and three hours after drug administration by cardiac puncture. Food was then offered ad libitum. One hour later the animals were sacrificed and their stomachs removed. The difference in wet weight between full and empty stomach was utilized to quantify the food intake. Median food intake was 0.3877 g for the fish treated with 2-DG and 0.107 g for the animals injected with saline. This difference was statistically significant by the Mann-Whitney test (P<0.05). The median values of blood glucose levels before drug injection were 46.19 mg/100 ml in the 2-DG-treated fish and 44.54 mg/100 ml in the control group. Three hours after drug administration, the values were 48.64 mg/100 ml in the experimental group and 56.90 mg/100 ml in the control group. The difference between the values of blood glucose before and after the drug was not significant for either group. We conclude that glucoprivation provokes food intake in fish and that the same glucoprivation was not sufficient to provoke hyperglycemia.
Keywords: FOOD INTAKE; 2-DEOXYGLUCOSE; GLYCEMIA; NILE TILAPIA-ALEVINS